2019
DOI: 10.1159/000495467
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin Attenuates Neuroinflammation in Traumatic Brain Injury in Young Rats

Abstract: Objectives: Inflammation and apoptosis play a critical role in the pathological progress of traumatic brain injury (TBI). Isoliquiritigenin is a bioactive component extracted from licorice roots, which possesses anti-inflammatory and anti-apoptotic properties. This study aims to investigate the potential effects of isoliquiritigenin on neuroinflammation in a rat model of TBI. Methods: The SH-SY5Y cells were subjected to cell injury induced by shear stress and the effect of isoliquiritigenin on cell apoptosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Physical and cognitive deficits result from both primary injury to the trauma site and delayed secondary injury to surrounding structures. Neuroinflammation is a major pathogenic mechanism for secondary brain injury following TBI (Chiu et al, 2016;Simon et al, 2017;Liu et al, 2019), characterized by edema, microglial and astrocytic activation and migration, and the release of inflammatory cytokines and chemokines (Gyoneva and Ransohoff, 2015;Karve et al, 2016;Webster et al, 2017). Thus, inhibition of these processes following sTBI may significantly reduce the progressive deficits associated with secondary brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Physical and cognitive deficits result from both primary injury to the trauma site and delayed secondary injury to surrounding structures. Neuroinflammation is a major pathogenic mechanism for secondary brain injury following TBI (Chiu et al, 2016;Simon et al, 2017;Liu et al, 2019), characterized by edema, microglial and astrocytic activation and migration, and the release of inflammatory cytokines and chemokines (Gyoneva and Ransohoff, 2015;Karve et al, 2016;Webster et al, 2017). Thus, inhibition of these processes following sTBI may significantly reduce the progressive deficits associated with secondary brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is a complex injury with a number of symptoms accompanied by inflammatory process and cell death (Arciniegas, 2011; Liu et al, 2019). It is characterized by an initial neuroinflammation, mediated by a rapid glia cells activation, peripheral immune cells recruitment and secretion of inflammatory cytokines, followed by the late appearance of psychologically debilitating symptoms and cognitive impairments (Woodcock and Morganti-Kossmann, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that sulforaphane was able to not only reduce cathepsin B‐dependent NLRP3 inflammasome activation, but also downregulate STAT‐1 phosphorylation and activate Nrf2/HO‐1 cascade in Aβ‐treated THP‐1 macrophages. In chalcones, in vivo studies suggested isoliquiritigenin as a potent inhibitor of the NLRP3 inflammasome against ICH and TBI . Previous studies have also shown that isoliquiritigenin was a potent NLRP3 inflammasome inhibitor in different inflammatory disease models, including the high‐fat diet‐induced obesity and indomethacin‐induced small intestinal damage .…”
Section: Health Promoting Potentials Of Dietary Phytochemicalsmentioning
confidence: 99%
“…In chalcones, in vivo studies suggested isoliquiritigenin as a potent inhibitor of the NLRP3 inflammasome against ICH and TBI. [149,150] Previous studies have also shown that isoliquiritigenin was a potent NLRP3 inflammasome inhibitor in different inflammatory disease models, including the high-fat diet-induced obesity and indomethacin-induced small intestinal damage. [151,152] Finally, emerging data has also shown that the plant-derived phytochemicals besides flavonoids, terpenoids, saponins, and curcuminoids, also exerted health promoting potentials to prevent neurological disorders, especially depression ( Table 1).…”
Section: Othersmentioning
confidence: 99%